Reflexions on multidisciplinarity and geologic risk management in Cuba - Galbán Rodríguez Liber; Vidaud Quintana Ingrid N.; Chuy Rodríguez Tomás Jacinto; Ruiz Ruiz José María; Calderín Mestre Francisco; Alvarez Deulofeu Eduardo Rafael (Earth Sciences Research Journal)
Geological risk management has special relevance in construction and the creation of new infrastructure in Cuba. The aim of this work was to focus on making some reflections about the multidisciplinarity analysis of geological risk management in the country from a critical perspective